APPLICATION OF SUPPORT VECTOR MACHINE METHOD FOR RUPIAH EXCHANGE RATE TO US DOLLAR FORECASTING - Rias Monica Putri; Edy Widodo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
A country’s currency exchange rate is one of important indicators in economy. The currency used in international transactions is called Foreign Exchange. For a developing country like Indonesia, the role of foreign exchange rate is very important, especially against hard currencies such as US Dollar. Forecasting foreign exchange is a very important strategy to achieve international business success. This study uses Support Vector Machine (SVM) method because that method has excellent capability in minimizing classification error. From this study result, obtained that the best parameter to forecast Rupiah exchange rate to US Dollar are epsilon (ε) = 0.1, cost (C) = 256, and gamma (γ) = 8. Then, the result of Rupiah exchange rate to US Dollar forecasting on 14th days, the Rupiah exchange rate to US Dollar began to strengthen until it reached Rp. 14.359,14. Keywords:Foreign Exchange,Rupiah, US Dollar, Support Vector Machine (SVM)